Criticism of Musa Jarullah Bigiev's view of Universal Salvation by the Journal “Dîn wa Maʿishah” - Jamalov , Mubariz (Scholarya Demo Journal of Ruby, 2024)
With the influence of the civil wars that emerged during the reign of Ali, issues such as great sin, the relationship between faith and deeds, destiny, and freedom of will have been discussed since the early periods of Islam. Although the belief in the hereafter, which is one of the core principles of Islam, is accepted by all sects, some issues related to the details have been the subject of dispute throughout history. In this context, the status of non-Muslims in the hereafter and the eternity of hell have also been discussed and important literature has been formed on this subject. According to the general acceptance, those who do not accept Islam, the last divine religion, will remain in Hell for eternity. However, some scholars have argued that Allah will forgive all people and that Hell is not eternal, claiming that all people will eventually go to Paradise. In the last centuries, this forgotten issue was revived by innovators such as Rashid Riḍa and Shihab al-Din al-Marjani. Musa Jarullah Bigiev, one of the innovative thinkers of the twentieth century, also brought this issue to his agenda, which he called universal salvation. Musa Jarullah Bigiev first began to explain his view of universal salvation, which meant that all human beings would eventually go to paradise, in his lectures at Hussainia madrasah. Despite his close friends' warnings that this issue would lead to unnecessary discussion, Musa Jarullah Bigiev affirmed his belief in the issue's importance and its need for explanation. Finally, Musa Jarullah Bigiev began to publish his views on universal salvation in the form of serial articles in the journal Shura, and his arguments were subjected to harsh criticism by the authors of the journal Din wa Maʿishah. The discussions at first, began with journal articles and progressed to treatises. The discussions between Musa Jarullah Bigiev and the writers of the journal Din wa Maʿishah were mainly focused on various issues such as the all-encompassing nature of divine mercy, non-believers and superstitious people going to paradise, and the eternity of hell.